Study the Effect of Fillers and Thermoplastics Content in the Mechanical Properties of Natural Rubber Vulcanized - Muter, Mohammed A.; Mugar, Qusay K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research, the mechanical properties of natural rubber blends in different proportions (70:30, 85:15, 100: 0 55:45 and phr) was studied through the use of two types of fillers (carbon black and titanium dioxide Nano) which show through tests conducted on the prepared models that increase fillers content which leads to improve the tensile properties (tensile strength, elastic modulus, elongation, hardness and compressibility). As shown by the results that the presence of polypropylene (PP) in the mix combination works to reduce the degree of intumescent and increase its content in the composition of mixtures which leads to get a great resistance to chemicals (acids, bases and oils).